L’acquisto a non domino dei beni mobili nell’ordinamento tedesco tra diritto germanico e tempi moderni - Gröschler, Peter (Cultura giuridica e diritto vivente, 2020)
[The acquisition of movable property in good faith in the German legal system between Germanic law and modern times]. The current regulatory system of purchase from the non-authorised person in the German Civil Code (BGB) is a combination of various historical elements, some of which are contradictory. The BGB attempts to reconcile these elements even though this cannot be achieved completely. Nevertheless, the more than 120 years since the BGB came into effect show that it is a functioning regulation.